Hereditary Hyperferritinemia-Cataract Syndrome in 3 Generations of a Family in East Tennessee - Heidi A. Worth; Zachary Marlette; David Aljadir; Ronald Lands (Case Reports in Hematology)
Hereditary hyperferritinemia and cataracts syndrome (HHCS) without iron overload is a syndrome first identified less than 3 decades ago. While investigators have dissected the gene where several responsible mutations reside, it remains a relatively unknown genetic disorder to clinicians. The result is often an expensive, invasive evaluation for iron overload, followed by a well-intended prescription for a series of phlebotomies that delivers morbidity instead of benefit. We present a father with an elevated ferritin and heterozygosity for H63D HFE mutation whose clinical course followed this path. His treatment rendered him symptomatic from iron deficiency with no reduction in his ferritin. On re-evaluation, a review of his past medical history clarified the cataract surgery noted in his record had occurred at a young age. Furthermore, one of his daughters required cataract surgery as a teenager. With this information, we strongly suspected HHCS. His phlebotomies were discontinued, and within weeks, his iatrogenic iron deficiency resolved and his health returned to normal.